(3GdEaGOI hGdJHUjQ dcd QGe eHJOF Ch eGgQ JMQjQ HGdSge GdWhjd hGdbUjQs - (3ejehf Hf YHO Gddg, YHO Gddgs
(3ChdgG (B:s
(3ai SHjdI HOQLI ai GdLfI CeG HYO , aEfg deG cGf GdLgGO ef CYXe GdYHGOGJ , hcGf aQV Yjf ajeG bjd s
(3BNQgG (B:s
(3ced GdcJGH HMeO Gddg JYGdi hMSf Yhfg hJhajbg hgh MSHi hfYe Gdhcjd eHGQckG Edi jhe GdOjf s
(3fSNI NRGFfjIs
(3HQSe GdNRGfI GdYGdjg GdehdhjI CejQ Ydi Hf GdebQ GdeQMhe GdHOQi CejQ eSYhO Hf NWjQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B906 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B4 s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs